O2-S2.05 Start with the social determinants of health to tailor sexual health promotion for First Nations, Inuit and Métis youth in Canada. (10th July 2011) - Seto, J; Asfaw, T; Folz, K; Clark, W; Deleary, M; Sheikh, A
Abstract : Background: Sexual health promotion and approaches for the prevention of sexually transmitted and blood-borne infections (STBBI) should be tailored to the needs and realities of youth. Engaging youth and building their capacity is an important step in health promotion and has proven to be critical in the development of a promising initiative aimed at engaging First Nations, Inuit and Métis youth in Canada. Methods: Community consultative processes were used to engage First Nations, Inuit and Métis (FN/I/M) youth in the development of sexual health promotion and STBBI prevention approaches. Engagement began in 2008 through the establishment of a steering committee, which included FN/I/M youth stakeholders, with representatives from governmental and non-governmental agencies. The steering committee aimed to make effective use of relevant technologies and social media to reach and engage FN/I/M youth in Canada. In 2009, a workshop was held to enhance the involvement of youth to identify priorities for STBBI messaging and explore the best mediums to reach youth. The outcomes of this consultation process informed the development of capacity building social media pilot projects to reach FN/I/M youth. Results: FN/I/M youth identified the importance of taking a holistic approach by viewing sexual health through the lens of social determinants. Youth highlighted poverty, social support networks and education as major influences on sexual health outcomes for their peers. Key challenges youth noted included the lack of sexual health education and the need to strengthen social support networks. By tying in these determinants into promotion, youth identified themes such as addressing homophobia, and raising the importance of cultural relevancy to de-stigmatise sexual health within FN/I/M communities and to help youth to relate closer to messages. Youth also indicated that peer-to-peer social media methods were an ideal mechanism to convey messages. Many youth from across Canada were engaged in developing their own STBBI messages. Conclusions: Engaging FN/I/M youth as partners from concept onwards has led to an informed approach to the development of sexual health promotion and STBBI prevention messaging. Public health practitioners learnt youth need to be involved to gain credibility within this population, youth capacity building is important and taking a holistic social determinants approach in conceptualising messages is critical when reaching FN/I/M youth.